Atividades bioquímicas de isolados amazônicos de Trichoderma, ação antagônica ao Fusarium brasiliense e efeito bioestimulante em plantas de soja - Rodrigues, Cleverson [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
É necessário aumentar a produção de alimentos para atender o aumento da população mundial. A aplicação de fungicidas é um dos principais gastos na produção de alimentos. São necessárias alternativas de controle que visem reduzir a agressividade dos patógenos e melhorar o desempenho do vegetal de forma eficiente com redução dos danos ao meio ambiente. Agentes de biocontrole como os fungos antagonistas do gênero Trichoderma desencadeiam inúmeras reações fisiológicas, bem como indução de resistência e promoção de crescimento do vegetal, garantindo assim a produtividade das culturas. O Trichoderma tem a capacidade de produção de metabólitos antifúngicos, enzimas hidrolíticas da parede celular como proteases e glucanases. Além disso, o Trichoderma é capaz de realizar a disponibilização de fósforo (fosfatases ou ácidos orgânicos), absorção e disponibilização de ferro (sideróforos), ou ainda promover crescimento através de ação indireta. A aplicação do Trichoderma na agricultura tem promovido o crescimento de plantas pela produção de fitohormônios e indois relacionados ao ácido indolacétil, ácido salicílico, ácido jasmônico, etileno e indução do sistema de defesa da planta pelo aumento da atividade da quitinase e peroxidase, cuja resposta imune é dependente da cepa, concentração, duração da interação e do estado de desenvolvimento e órgão da planta. Essa revisão de literatura compila e sumariza os principais mecanismos de ação de Trichoderma atrelados ao biocontrole e seus efeitos fisiológicos como estimulantes do crescimento e rendimento produtivo das culturas agrícolas.

It is necessary to increase food production to meet the increase in world population. The application of fungicides is one of the main expenses in food production. Control alternatives are needed t hat aim to reduce the aggressiveness of pathogens and improve plant performance efficiently with reduced damage to the environment. Biocontrol agents such as antagonistic fungi of the genus Trichoderma trigger numerous physiological reactions, in addition to inducing resistance and promoting plant growth, thus ensuring crop productivity. Trichoderma has the ability to produce antifungal metabolites, cell wall hydrolytic enzymes such as proteases and glucanases. Furthermore, and glucanases. Furthermore, TrichodermaTrichoderma is capable of making is capable of making phosphorus available phosphorus available (phosphatases or organic), absorbing and making iron available (siderophores), or even (phosphatases or organic), absorbing and making iron available (siderophores), or even promoting growth by indirect action. The application of promoting growth by indirect action. The application of Trichoderma Trichoderma in agriculture has in agriculture has promoted plant growth through the production of phytohormonespromoted plant growth through the production of phytohormones and indoles related to and indoles related to indoleacetic acid, salicylic acid, jasmonic acid, ethylene and the induction of the plant's defense indoleacetic acid, salicylic acid, jasmonic acid, ethylene and the induction of the plant's defense system by increasing the activity of chitinase and peroxidase, whose immune system response system by increasing the activity of chitinase and peroxidase, whose immune system response depends on the strain, concentration, dudepends on the strain, concentration, duration of interaction, developmental state and organ of ration of interaction, developmental state and organ of the plant. This literature review compiles and summarizes the main switches of action of the plant. This literature review compiles and summarizes the main switches of action of TrichodermaTrichoderma and linked to biocontrol its physiological effects as growth stimulants and and linked to biocontrol its physiological effects as growth stimulants and productive yield of agrproductive yield of agricultural crops.icultural crops.
Biochemical activities of amazonian isolates of Trichoderma, antagonical action to Fusarium brasiliense and biostimulant effect on soybean plants
Keywords: Bioprospecção; Antagonismo; Bioestimulante; Microbioma; Controle biológico; Glycine max